Satisfaction and problems experienced with wrist movements: comparison between a common body-powered prosthesis and a new biomechatronics prosthesis - Abd Razak, N.A.; Abu Osman, Noor Azuan; Kamyab, M.; Wan Abas, W.A.B.; Gholizadeh, H. (Lippincott, Williams & Wilkins, 2014)
This report compares wrist supination and pronation and flexion and extension movements with the common body-powered prosthesis and a new biomechatronics prosthesis with regard to patient satisfaction and problems experienced with the prosthesis. Fifteen subjects with traumatic transradial amputation who used both prosthetic systems participated in this study. Each subject completed two questionnaires to evaluate their satisfaction and problems experienced with the two prosthetic systems. Satisfaction and problems with the prosthetic's wrist movements were analyzed in terms of the following: supination and pronation; flexion and extension; appearance; sweating; wounds; pain; irritation; pistoning; smell; sound; durability; and the abilities to open a door, hold a cup, and pick up or place objects. This study revealed that the respondents were more satisfied with the biomechatronics wrist prosthesis with regard to supination and pronation, flexion and extension, pain, and the ability to open a door. However, satisfaction with the prosthesis showed no significant differences in terms of sweating, wounds, irritation, pistoning, smell, sound, and durability. The abilities to hold a cup and pick up or place an object were significantly better with the body-powered prosthesis. The results of the survey suggest that satisfaction and problems with wrist movements in persons with transradial amputation can be improved with a biomechatronics wrist prosthesis compared with the common body-powered prosthesis.